The Brain Retains: Nonhuman Primate Models for Pediatric HIV-1 in the CNS - Obregon-Perko, Veronica (Curr HIV/AIDS Rep, 2020)
PURPOSE OF REVIEW: Perinatal HIV-1 infection is associated with an increased risk for neurologic impairments. With limited access to clinical specimens, animal models could advance our understanding of pediatric central nervous system (CNS) disease and viral persistence. Here, we summarize current findings on HIV-1 CNS infection from nonhuman primate (NHP) models and discuss their implications for improving pediatric clinical outcomes. RECENT FINDINGS: SIV/SHIV can be found in the CNS of infant macaques within 48 h of challenge. Recent studies show an impermeable BBB during SIV infection, suggesting neuroinvasion in post-partum infection is likely not wholly attributed to barrier dysfunction. Histopathological findings reveal dramatic reductions in hippocampal neuronal populations and myelination in infected infant macaques, providing a link for cognitive impairments seen in pediatric cases. Evidence from humans and NHPs support the CNS as a functional latent reservoir, harbored in myeloid cells that may require unique eradication strategies. SUMMARY: Studies in NHP models are uncovering early events, causes, and therapeutic targets of CNS disease as well as highlighting the importance of age-specific studies that capture the distinct features of pediatric HIV-1 infection.